Presidential Threshold: Harapan dan Tantangan Bacalon Presiden 2024 - Muhammad Lutfi; Mochamat Nurdin; Sumardi Sumardi; Baharuddin Baharuddin (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
This paper aims to analyze how the government's level of satisfaction has so far been and how the inevitability of prospective leaders who will compete in the 2024 election celebrations for newcomers. The methodology used in this study uses a library research approach, starting with a search for articles using the keywords of government policies in the fields of economics, law, social and democratic and political dynamics ahead of the 2024 elections in the Scopus and Google Scholar the 2015-2022 period and then reviewedbased on four stages, including: 1) Search for articles, 2) Mapping discussion topics, 3). Topic analysis, and 4). Further analysis with the support of credible data that has been published by credible survey institutions. The results of the study and analysis concluded that the hope of bringing in future leaders still reaps pessimism, this happens because in public reading of their satisfaction with the government's performance, in this case the Jokowi-Ma'ruf cabinet, which is already in its third year, is currently considered to have failed to control the government. policy on a number of aspects, especially regarding the fulfillment of public needs, and economic investment, then another challenge is political and democratic disruption, the existence of a presidential threshold will have an impact on the leadership relay which has an oligarchic background and network similar to the political strategy played by elites and political parties. so far. S